(untitled) (Scientific journal of the Fergana State University, 2023)
This article is about how reading is one of the most significant processes of our life. Reading and it’s strategies are used in the class in order to make lesson easier and enhance reading comprehension and vocabulary knowledge. You have to take into consideration your students’ ability and their age in choosing reading strategies and activities.